Is There a Kurdish Village? Thinking with Stirling and Reflecting on Kurdish Rural Settlements of the Last Century - Yalcin-Heckmann, Lale (My University, 2023)
Paul Stirling’s Turkish Village (1965) has been seminal for anthropologists studying rural life in Turkey in the second half of the 20th century. This contribution examines the intellectual and anthropological impact of Stirling's work on studying Kurdish rural settlements. It aims to reflect on and compare it with the author’s own work Tribe and Kinship among the Kurds (1991). Kurdish tribal relations were the focus of this work, and at the time political relations seemed more important than rural economy. A more careful comparison of the two works sheds further light on their weaknesses as well as strengths.
Existuje kurdská vesnice? Myšlení se Stirlingem a reflexe kurdských venkovských sídel minulého století
Keywords: Social Anthropology; Paul Stirling; Turkey; Kurds; Kurdish rural settlements; Sociální antropologie; Paul Stirling; Turecko; Kurdové; Kurdské venkovské osady